Konsekuensi Budgetary Slack : Perspektif Gender: Consequences of Budgetary Slack: Gender Perspective - Suhartini, Dwi; Sari, Rida Perwita; Riadi, Eko (Journal of Accounting Science, 2019)
The purpose of this research is to examine the effect of participatory budgeting on budgetary slack behavior and managerial performance in the public sector. This study will include the personal character of gender and affective, continuance, normative organizational commitment in the relationship of participatory budgeting with the behavior of budgetary slack. This study uses the mail survey method with an individual analysis unit as an executive officer at the Regional Work Unit (SKPD) at the East Java Province level. Data obtained from 82 respondents' answers in the form of perceptions or attitudes to the variables under study. The sampling technique with sampling census and analysis techniques using PLS. The results showed that executive officials at SKPD actively involved in budgeting mechanisms tended to conduct budgetary slack behavior which was motivated by the limited use of budget funds. However, this remains a trigger for managerial performance to remain high. High participatory budgeting can increase organizational commitment and gender roles can reduce budgetary slack behavior.